Optimizing Waste Management in Lhokseumawe City: a GIS-Based Needs Assessment for Collection Facilities to Mitigate Illegal Dumping - Nanda Savira Ersa; Herman Fithra; Syibral Malasyi; Eva Lestari; Mukhlis; Zara Yunizar (International Journal of Marine Engineering Innovation and Research, 2025)
Solid waste management is a significant urban issue in Indonesia. This is exacerbated by rapid population growth and urbanization, which are not accompanied by sound waste management practices, such as a lack of infrastructure and widespread illegal dumping. This paper presents a data-driven methodology for analyzing trash generation patterns and identifying infrastructure requirements using a Geographic Information System (GIS). The goal is to create a data-driven strategy for identifying optimum Waste Collection Locations (WCPs) in order to improve service efficiency and reduce environmental impact. The study results show that Lhokseumawe City produces 530 m³ of waste daily. Therefore, Lhokseumawe City requires 44 strategically located waste disposal sites, taking into account existing illegal dumping locations and population density. An additional 21 garbage trucks are also needed to manage the urban waste generation volume. This indicates a significant shortage of waste management facilities to serve the population. This study presents a practical plan for local governments, including optimal WCP locations and designs, to achieve the SDGs goal of becoming a sustainable city.